2010
DOI: 10.1093/ejechocard/jeq081
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of apical rocking: a new, integrative approach for selection of candidates for cardiac resynchronization therapy

Abstract: Apical rocking is a new marker to assess LV dyssynchrony and predict CRT response. It is superior to conventional parameters. Even its simple visual assessment may be sufficiently accurate in the clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 32 publications
4
51
0
Order By: Relevance
“…In this field echocardiography may have a role in selection of patients based in small trials [16][17][18][19]21] which have shown that different dyssynchrony indices in patients with QRSd> 120 ms can have significant predictive value for CRT response. Furthermore, in the large CARE -HF trial [7], mechanical dyssynchrony, as assessed by echocardiography, was an inclusion criterion for patients with QRSd between 120 and 150 ms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this field echocardiography may have a role in selection of patients based in small trials [16][17][18][19]21] which have shown that different dyssynchrony indices in patients with QRSd> 120 ms can have significant predictive value for CRT response. Furthermore, in the large CARE -HF trial [7], mechanical dyssynchrony, as assessed by echocardiography, was an inclusion criterion for patients with QRSd between 120 and 150 ms.…”
Section: Discussionmentioning
confidence: 99%
“…Szulik et al [18] tested a novel echocardiographic measurement of LV dyssynchrony by analysing apical rocking. They used apical transverse motion (ATM) as a marker of apical motion perpendicular to the LV long-axis and this was calculated in each apical plane (A4C, A3C and A2C) as the average of the integrated longitudinal myocardial velocity curves from the two opposite apical segments.…”
Section: Mechanical Dyssynchrony In Patients With Significant Electrimentioning
confidence: 99%
“…Many researchers suggested using visual markers of cardiac motion including apical rocking and septal flash as indicators for dyssynchrony [18, 19]. However, dyssynchrony is often subtle, and so it cannot be quantified by visual assessment alone.…”
Section: Patterns Of Motion and Deformationmentioning
confidence: 99%
“…However, dyssynchrony is often subtle, and so it cannot be quantified by visual assessment alone. Quantitative tools should be used to complement the visual description of myocardial deformation [18-20]. …”
Section: Patterns Of Motion and Deformationmentioning
confidence: 99%
“…Although RSDc or radial discoordination index method seems more logical and more practical than time-based dyssynchrony, they need to be validated by multicenter trials and compared with other possible parameters such as apical rocking motion, which can be quickly assessed visually. 17 It will take some time for the CRT community to have confidence in an echocardiographic parameter to be used for the selection of patients for CRT. We now have learned that any future echocardiography parameter for prediction of CRT response should use the concept of wasted energy and not rely on temporal dyssynchrony alone, as Kydd et al 10 demonstrated.…”
mentioning
confidence: 99%